2006
DOI: 10.1007/s10151-006-0286-x
|View full text |Cite
|
Sign up to set email alerts
|

The place for colectomy and ileorectal anastomosis: a valid surgical option for ulcerative colitis?

Abstract: Employed on a selective basis, IRA is a safe procedure with low mortality and morbidity and good prospects for success in many patients with UC. The patients must be prepared to submit to life-long rectoscopy surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 23 publications
2
23
1
5
Order By: Relevance
“…However, these data are not confirmed by more recent experiences [2, 3, 18]. Even if in literature rectal compliance is not a validated parameter for the postoperative development of intractable proctitis, in our opinion it is one of the most important features to indicate IRA.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…However, these data are not confirmed by more recent experiences [2, 3, 18]. Even if in literature rectal compliance is not a validated parameter for the postoperative development of intractable proctitis, in our opinion it is one of the most important features to indicate IRA.…”
Section: Discussioncontrasting
confidence: 61%
“…It was shown that dysplasia in the rectum progressively increases from 9% at 10 years to 25% at 20 years after IRA [5]. However, the overall incidence of rectal cancer after IRA varies in literature, ranging from 0 to 8% [2, 3, 5, 6, 19]. Lepistö and Järvinen and Leijonmarck et al reported an incidence of 0%, respectively, in 20 and 51 patients, after a mean follow-up of 18 and 13 years, respectively [2, 6].…”
Section: Discussionmentioning
confidence: 99%
“…There is a physiological decrease in sphincter function in older persons, which may lead to worse bowel control. These observations led some authors to recommend ileo-rectal anastomosis in elderly UC patients [14,15]. …”
Section: Discussionmentioning
confidence: 99%
“…248 the benefits of total abdominal colectomy with ileoproctostomy are its relative simplicity and predictability compared with iPaa. [250][251][252][253] in addition, the theoretical risk of developing cancer in the remaining rectum should be considered when counseling the patient about surgical options. 249 the disadvantages are related to the long-term durability of the procedure.…”
Section: Total Abdominal Colectomy With Ileoproctostomy Maymentioning
confidence: 99%